Implementasi Kebijakan Program Keluarga Harapan di Desa Bongoime Kecamatan Tilongkabila Kabupaten Bone Bolango - Basalama, Fitria Ananda; Igirisa, Irawaty; Tuhopi, Rustam (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of the research is to determine: Implementation of the Family Hope Program (PKH) Policy in Bongoime Village, Tilongkabila District, Bone Bolango Regency, with research sub-focuses namely: Communication, Resources, Disposition/Attitude of Implementers and Bureaucratic Structure. This research approach The type of research in this thesis is Qualitative Descriptive Research. Qualitative descriptive research is a type of research that observes and captures factually and actually the real world and examines the behavior of individuals, groups and their daily experiences, as well as studying, explaining or interpreting a case in its context naturally without any intervention from outside parties. Based on the results of the Family Hope Program Implementation Process in Bongoime Village, Tilngkabila District, Bone Bolango Regency, it was deemed necessary to improve the Implementor in several aspects, namely, Communication, resources, attitude of the implementer, and Bureaucratic structure so that the Implementation of this policy is achieved in accordance with the stated objectives. desired. This implementation process is measured by aspects of communication, resources, disposition/attitude of implementers and bureaucratic structure and is assessed as being in accordance with existing regulations.